The Translation Procedure Two English Translated Song Versions: A Case Study on Japanese Song “Ano Yume Wo Nazotte” by Yoasobi - Vincensius Radhitya Trisnabudi; Harris Hermansyah Setiajid (Universitas Muhammadiyah Semarang, 2022)
Translation is one of the media to provide understanding to other language users. One of the media often translated is a song. Song is a medium that is not limited by distance and language. Some of the songs have been translated into several languages. In translating the song, there are two possible versions of the translation. The first is a direct translation, that is, a translation meant to find out the meaning of the song from the source language (SL) to the target language (TL). The second is a translated version which can be performed for commercial purposes. Both have different procedures in translation. It is, therefore, challenging to examine the translation procedures applied to see the differences in how both versions are rendered. In this research, the object of the study is the Japanese song “Ano Yume wo Nazotte” by Yoasobi. This song has two English-translated versions. The first is a literal or direct translation and a translation specifically for singing. Vinay & Darbelnet’s SCFA translation procedures are applied in this research to reveal the procedures in these two versions of the translation. This research found that in the direct translation of the song, the procedure that is commonly used is transposition. As the sentence structures between the Japanese language and English are different, the use of transposition becomes dominant. Meanwhile, the translation created specifically for singing also has transposition as the dominant procedure, but this version also widely uses the inversion procedure to maintain the natural aspect of the TL. From this research, we can see that the transposition procedure is the most appropriate procedure for translating a text with different structures in their SL and TL, and if the purpose of translation is to maintain its sing ability, the procedure applied is inversion.